2003
DOI: 10.1016/s1044-0305(03)00125-9
|View full text |Cite
|
Sign up to set email alerts
|

Investigative proteomics: Identification of an unknown plant virus from infected plants using mass spectrometry

Abstract: We describe the identification of a previously uncharacterized plant virus that is capable of infecting Nicotiana spp. and Arabidopsis thaliana. Protein extracts were first prepared from leaf tissue of uninfected tobacco plants, and the proteins were visualized with two-dimensional electrophoresis (2-DE). Matching gels were then run using protein extracts of a tobacco plant infected with tobacco mosaic virus (TMV). After visual comparison, the proteins spots that were differentially expressed in infected plant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
63
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(63 citation statements)
references
References 23 publications
(21 reference statements)
0
63
0
Order By: Relevance
“…Parent peptide mass error tolerance was set at 2.0 amu and fragment ion mass tolerance was set at 1.0 amu during the search. The criteria used for a preliminary positive peptide identification are the same as previously described, namely a dCn score Ͼ 0.08, and Xcorr Ͼ1.8 for ϩ1, Xcorr Ͼ2.5 for ϩ2, and Xcorr Ͼ3.5 for ϩ3 charged peptide precursor ions (16). Peptides matching proteins of interest were confirmed by visual examination of the spectra.…”
Section: Methodsmentioning
confidence: 99%
“…Parent peptide mass error tolerance was set at 2.0 amu and fragment ion mass tolerance was set at 1.0 amu during the search. The criteria used for a preliminary positive peptide identification are the same as previously described, namely a dCn score Ͼ 0.08, and Xcorr Ͼ1.8 for ϩ1, Xcorr Ͼ2.5 for ϩ2, and Xcorr Ͼ3.5 for ϩ3 charged peptide precursor ions (16). Peptides matching proteins of interest were confirmed by visual examination of the spectra.…”
Section: Methodsmentioning
confidence: 99%
“…In-gel digestion and nano high performance liquid chromatography (HPLC) followed by tandem mass spectrometry (MS/MS) were performed as described (Breci et al, 2005). Briefly, gel slices were destained (Breci et al, 2005;Cooper et al, 2003) and digested with trypsin (Wilm et al, 1996). The tryptic peptides were extracted with 5% formic acid/50% CH 3 CN.…”
Section: Protein Identificationmentioning
confidence: 99%
“…Traditional diagnostic methods of symptom evaluation, vector specificity, host range studies, and electron microscopy to visualize particle and inclusion size and shape tend to be more generic than molecular methods. Often, two or more assays are combined as part of the diagnosis process (Cooper et al, 2003).…”
mentioning
confidence: 99%
“…By using an appropriate scoring algorithm, the closest match or matches are identified. Cooper et al (2003) identified Tobacco mosaic virus and Potato virus X using two-dimensional SDS PAGE to compare proteomes of infected and Page 6 of 18 A c c e p t e d M a n u s c r i p t uninfected plant tissues. Differential spots were excised, digested by trypsin, analyzed by MALDI-TOF MS and PMFs generated.…”
mentioning
confidence: 99%
See 1 more Smart Citation